1991
DOI: 10.1002/tox.2530060213
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of domestic water heaters with Legionella pneumophila: Impact of water temperature on growth and dissemination of the bacterium

Abstract: ~ ~~Sediment and tap water from 255 randomly selected domestic water heaters were cultured on buffered charcoal yeast extract agar and two semiselective media to detect the presence of Legionellaceae. Different serogroups of L . pneumophila, the only species of Legionellaceae identified in this study, were found in 84 of the 255 water heaters and this contamination occurred only in electric water heaters ( n = 205). Sediment contamination by L . pneumophila was strongly associated with water temperature. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In other studies electric hot-water heaters were much more likely to be contaminated with legionellae than oil or gas-fired heaters [13,14]. De Waelly and Joly found that 84 of 255 (33 %) of domestic hot-water heaters in three towns in the Quebec City area were contaminated with legionellae [14]. In another study Alary and Joly found that 69 of 178 (39%) of Quebec City homes with electric hot-water heaters were colonized by legionellae [13].…”
Section: T Marrie and Othersmentioning
confidence: 99%
“…In other studies electric hot-water heaters were much more likely to be contaminated with legionellae than oil or gas-fired heaters [13,14]. De Waelly and Joly found that 84 of 255 (33 %) of domestic hot-water heaters in three towns in the Quebec City area were contaminated with legionellae [14]. In another study Alary and Joly found that 69 of 178 (39%) of Quebec City homes with electric hot-water heaters were colonized by legionellae [13].…”
Section: T Marrie and Othersmentioning
confidence: 99%
“…In Quebec, water heaters, as well as institutional, commercial or residential hot water distribution systems, are known as reservoirs involved in the dispersion of Legionella bacteria [8]. Indeed, it was reported that 33% of electrical water heaters were colonized by Legionella, with concentrations from 10 to more than 100 CFU/mL [11].…”
Section: Introductionmentioning
confidence: 99%
“…Electric water heaters are by design thermally stratified, unlike oil and gas water heaters and are therefore more susceptible to Legionella contamination [11,[35][36][37][38][39]. This is attributed to the lower temperatures in the bottom of the water heater caused by thermal stratification and the presence of sediments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, natural gas heating in non-scaling waters tends to break up stratification typical of electric heaters due to heating from the bottom of the tank; however, in scaling waters, the internal insulating properties of thick scale may induce stratification in gas heaters by reducing heat transfer to the tank ( Figure 5). In non-scaling waters, occurrence of L. pneumophila was dramatically higher in electric tanks versus natural gas as a result of stratification ( Table 2), but with high scaling, this benefit might not be significant [21,34] Additionally, gas-fired systems typically cost less to operate than electric storage tanks if operating at full efficiency.…”
Section: Electric Versus Gas Tanksmentioning
confidence: 99%